Veterinary clinic management system with SMS notification / Nur Fatihah Nadirah Ali - Ali, Nur Fatihah Nadirah (2017)
Nowadays, information system play an important role to the business organization as it support the operations and decision making within the organization. Healthcare is the one of organization that need information system in other to improve the quality of care. However, not all healthcare organization in Malaysia implementing the information system such as veterinary clinic. The problems had been identified based on the interview session with the staff of the Family Veterinary Clinic and the researcher successful resolve the problem. All of the problem facing by the stakeholder is due to the manual system that handle the clinic daily operation. Hence, the problem faced by the clinic are difficulty in organize patient’s information as the patients need to fill up the registration form manually and the data are kept on file and stored in the cabinet. Another problem facing by the clinic are difficulty in checking the availability of the appointment which the staff need to record the appointment information in the appointment book. The last problem faced by the clinic is difficulty in calculating medicine stock as the staff need to manually count the quantity of the medicine. When the certain medicine reached a minimum quantity the staff need to order with the supplier. Therefore, one of the solutions is to develop the clinic management system for the Family Veterinary Clinic. In other to develop a system, there are four objectives that need to be achieve which are to gather and analyze requirements from the Family Veterinary Clinic, to design the veterinary clinic management system with SMS notification for Family Veterinary Clinic, to develop the veterinary clinic management system with SMS notification for Family Veterinary Clinic and to test the functionality of the web based the veterinary clinic management system for Family Veterinary Clinic. The methodology that will be used to achieve the objectives is iterative waterfall model. In this methodology, the four phase involves are requirement gathering and analysis, design, implementation and testing. This system cover all the basic module includes owner and pet management module, treatment module, appointment module and medicine stock module. A SMS reminder is added in this system as a feature to remind the patient that tends to forget their appointment. Hence, a Veterinary Clinic Management System is completely develop on web based application platform that have a SMS reminder feature.